Respuesta :
Complete Question
The complete question is shown on the first uploaded image
Answer:
First Question
Option A is correct
Second Question
Option C is correct
Third Question
[tex]D = A^{-1} * B^{-1} * C^{-1}[/tex]
Fourth Question
So substituting for D in (ABC) D = I
[tex](ABC) * A^{-1} * B^{-1} * C^{-1} = I[/tex]
[tex]I = I[/tex]
This proof that ABC is invertible
Step-by-step explanation:
From the question we are told that
A , B and C are invertible which means that [tex]A^{-1} , B^{-1}, C^{-1}[/tex] exist
Now
From the question
(ABC) D = I
Where I is an identity matrix
Now when we multiply both sides by [tex]A^{-1}[/tex] we have
[tex]A^{-1} A BCD = A^{-1} * I[/tex]
[tex]IBCD = A^{-1}[/tex]
Now when we multiply both sides by [tex]B^{-1}[/tex] we have
[tex]B^{-1 } *I BCD = A^{-1} * B^{-1}[/tex]
[tex]I CD = A^{-1} * B^{-1}[/tex]
Now when we multiply both sides by [tex]C^{-1}[/tex] we have
[tex]C^{-1} * I CD = A^{-1} * B^{-1} * C^{-1}[/tex]
[tex]I D = A^{-1} * B^{-1} * C^{-1}[/tex]
[tex]D = A^{-1} * B^{-1} * C^{-1}[/tex]
So substituting for D in the above equation
[tex](ABC) * A^{-1} * B^{-1} * C^{-1} = I[/tex]
[tex]I = I[/tex]
This proof that ABC is invertible
![Ver imagen okpalawalter8](https://us-static.z-dn.net/files/d03/4d6021ef97e9d3c5c097072871b76ab4.png)